Methyl 6-O-cinnamoyl-α-d-glucopyranoside Ameliorates Acute Liver Injury by Inhibiting Oxidative Stress Through the Activation of Nrf2 Signaling Pathway - Xu, Qianqian; Deng, Yanfang; Ming, Jiaxiong; Luo, Zengwei; Chen, Xia; Chen, Tianqi; Wang, Yafen; Yan, Shan; Zhou, Jiajun; Mao, Lina; Sun, Weiguang; Zhou, Qun; et al. (Frontiers in Pharmacology, 2022)
Excessive stimulation of hepatotoxins and drugs often lead to acute liver injury, while treatment strategies for acute liver injury have been limited. Methyl 6-O-cinnamoyl-α-D-glucopyranoside (MCGP) is a structure modified compound from cinnamic acid, a key chemical found in plants with significant antioxidant, anti-inflammatory and antidiabetic effects. In this study, we investigated the effects and underlying mechanisms of MCGP on acetaminophen (APAP) or carbon tetrachloride (CCl4) induced acute liver injury. As a result, MCGP inhibited cell death and apoptosis induced by APAP or CCl4, suppressed the reactive oxygen species (ROS) generation stimulated by H2O2 in liver AML12 cells. In vivo, MCGP alleviated APAP/CCl4 induced hepatic necrosis, resumed abnormal aminotransferase activities and liver antioxidase activities. Besides, MCGP depressed APAP or CCl4 induced oxidative stress through the suppression of CYP2E1 and activation of the Nrf2 signaling pathway. MCGP also enhanced the number of PCNA-positive hepatocytes, increased hepatic PCNA and Bcl-XL, decreased BAX expression in APAP-/CCl4-intoxicated mice. Furthermore, MCGP activated the GSDMD-N/cleaved caspase 1 pathway. In summary, MCGP might act as potential therapeutic drug against drug-induced and chemical-induced acute liver injuries, and its underlying mechanisms might engage on the pressing of oxidative stress, refraining of hepatocyte apoptosis, and facilitating of liver regeneration.